Hybrid Tamm plasmon resonance excitation towards a simple and efficient biomedical detector of NaI solution. Issue 45 (11th October 2022) - Taha, T. A.; Elsayed, Hussein A.; Mehaney, Ahmed; Hajjiah, Ali; Ahmed, Ashour M.
Abstract : NaI sensor: the suggested design of a NaI photonic crystal sensor that is constituted. Abstract : This work presents a theoretical verification for the detection of Sodium iodide (NaI) solution with different concentrations in the vicinity of Tamm plasmon (TP) resonance. The proposed sensing tool is constituted of prism/Ag/cavity/(GaN/CaF2 ) 15 /air. The essential foundation of this study is based on the displacement of the TP resonance by varying the concentration of an aqueous solution of sodium iodide (NaI) that fills the cavity layer. The resonant TP dip is shifted downwards the shorter wavelengths with the increment of the Ag layer thickness. Nevertheless, the resonant TP dip is shifted upwards to longer wavelengths with the increment of NaI refractive index/concentration. Also, the sensitivity of the sensing tool decreases with the increment of the NaI refractive index. However, the minimum result is not less than the value of 9913 nm RIU −1 for a concentration of 25%. Finally, the performance of our sensor in the form of the quality factor, detection limit, and figure of merit showed significant improvements in designing a high-performance liquid and biosensor.